2005
DOI: 10.1080/00365520510023297
|View full text |Cite
|
Sign up to set email alerts
|

Saliva transport to the distal esophagus

Abstract: Saliva transport to the distal esophagus does not require complete normal peristalsis or gravity and mainly depends on an efficient pharyngeal pump. However, subjects in supine position with severe esophageal dysmotility might have both impaired volume clearance and delayed saliva transport, leading to abnormal acid clearance and esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
10
1
6
Order By: Relevance
“…These alterations in the distal esophagus do not delay the arrival of saliva to the distal esophageal body but prolong the clearance to the stomach in the supine position (14). In this situation the subjects may have more frequent and intense esophageal lesions caused by gastroesophageal reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations in the distal esophagus do not delay the arrival of saliva to the distal esophageal body but prolong the clearance to the stomach in the supine position (14). In this situation the subjects may have more frequent and intense esophageal lesions caused by gastroesophageal reflux.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in almost half of the reflux episodes in normal subjects (20). The clearance of acid volume from the distal esophagus may be compromised by the low contraction amplitude but the acid neutralization by saliva, that occurs with primary peristalsis, may be normal (14).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no relationship between ETT and the subjects' age, which can be explained by the fact that we generally evaluated only young and healthy subjects (mean age: 21.8 ± 1.5 years). However, more studies assessing the ETT in older subjects and patients with different pathologies, such as gastroesophageal reflux [12][13][14] , dysphagia [15,16] , esophagitis [17,18] , and achalasia [6,19,20] , are necessary to determine the differences in ETT of healthy subjects versus patients. It is likely that the ETT will differ in patients with a clinical diagnosis of esophageal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the scintigraphic technique is the gold standard test accepted to assess ETT and it is indicated in cases where the manometric and barometric studies do not give a differential diagnosis [11] . The ETT assessment is used to complete the diagnosis of diseases, such as gastroesophageal reflux [12][13][14] , dysphagia [15,16] , esophagitis [17,18] , and achalasia [6,19,20] . The latter studies are commonly performed with scintigraphic and manometric techniques [21] , in healthy [22] , geriatric [23] , and pediatric patients [24] , despite the use of ionizing radiation and catheters in each test, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…O material que reflui do estômago para o esôfago é novamente conduzido ao estômago por mecanismo denominado clareamento esofágico. O mecanismo é representado pela peristalse esofágica eficaz, gravidade e deglutição de saliva 15,16 . Vários autores demonstraram que, após um episódio de RGE, o tempo de clareamento esofágico é maior nos pacientes com esofagite do que em indiví-duos normais 15,17,18 .…”
Section: Introductionunclassified